2017
DOI: 10.1007/s12185-017-2379-x
|View full text |Cite
|
Sign up to set email alerts
|

NK cell therapy after hematopoietic stem cell transplantation: can we improve anti-tumor effect?

Abstract: After decades since the discovery of natural killer (NK) cells as potential effector cells fighting malignantly transformed and virally infected cells, little progress has been made in their clinical application. This yet unrealized therapeutic effect is presumably, at least in part, due to low numbers of functional NK cells that could be obtained from the peripheral blood relative to tumor burden. Our group hypothesized that a relatively small NK cell number to targeted malignant cells is the cause of a lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Autologous NK cells may be inhibited by “ self ” MHC-I, thus limiting GvT effects in the absence of exogenous cytokines or antibodies ( 265 , 266 ). Therefore, allogeneic NK cells along with hematopoietic stem cell transplant has been explored as a potential treatment for patients with high-risk solid tumors ( 263 , 267 , 268 ). Using non-myeloablative conditioning regimens to provide potent immune suppression without toxicity, the burden of cure then relies on the ability of transplanted donor cells to provide a GvT effect.…”
Section: Nk Cells In Health and Diseasementioning
confidence: 99%
“…Autologous NK cells may be inhibited by “ self ” MHC-I, thus limiting GvT effects in the absence of exogenous cytokines or antibodies ( 265 , 266 ). Therefore, allogeneic NK cells along with hematopoietic stem cell transplant has been explored as a potential treatment for patients with high-risk solid tumors ( 263 , 267 , 268 ). Using non-myeloablative conditioning regimens to provide potent immune suppression without toxicity, the burden of cure then relies on the ability of transplanted donor cells to provide a GvT effect.…”
Section: Nk Cells In Health and Diseasementioning
confidence: 99%
“…Donor selection was cited as a factor in a recent Phase II study which reported good safety and no GvHD, but no significant efficacy, in patients with relapse of persistent myeloid malignancies treated with haploidentical NK cells [70]. Though most of these studies were carried out in the context of hematologic malignancies, successes with solid tumors remain limited [71].…”
Section: Allogeneic Nk Cell Immunotherapymentioning
confidence: 99%
“…There are also a number of studies estimating the combination of HSCT and NK cell transplantation. Although the efficacy remains controversial, NK cell transplantation before or after HSCT was shown to be applicable without serious side effects [ 133 , 134 , 135 ]. A phase I/II clinical trial in which AML patients received haploidentical HSCT combined with early adoptive NK cell transfer demonstrated 37% of two-year overall survival compared to 14% for patients who underwent haploindentical HSCT, suggesting that transferred NK cells may contribute to long-term remission in patients with refractory AML [ 136 ].…”
Section: Current Approaches To Nk-cell-based Immunotherapymentioning
confidence: 99%